Exploring Figurative Language in Ariana Grande’s Interview on The Tonight Show with Jimmy Fallon - Dolun, Maria Magdalena Gelu; Handayani, Nurma Dhona (PROJECT (Professional Journal of English Education), 2025)
This research adopts a qualitative descriptive approach to explore the types of figurative language employed by Ariana Grande in her interviews with Jimmy Fallon, published in June 2024, following Perrine’s (2018) typology of figurative language. The data collection process followed the observational method and note-taking technique, enabling systematic gathering of instances of figurative language while preserving the authenticity of spoken interactions. The analysis employed the referential identity method and the contextual meaning technique, focusing on how linguistic expressions relate to their external contexts and uncovering the meanings behind figurative language. A total of 38 instances of figurative language were identified across various types, including 4 similes, 7 metaphors, 5 personifications, 4 apostrophes, 4 metonymies, 3 symbols, 4 overstatements, 3 understatements, and 4 ironies. Metaphors emerged as the most frequently appearing type, reflecting the complex emotional states and experiences that Grande expresses, which resonate with her audience. Interestingly, no instances of allegory or paradox were found, suggesting that while the dialogue was rich in imagery and emotional depth, it did not engage in these more complex forms of figurative language. The findings underscore the expressive potential of figurative language in conveying nuanced interpersonal relationships and experiences.